Exhaled Molecular Fingerprinting in Diagnosis and Monitoring: Validating Volatile Promises. Issue 10 (October 2015) - Boots, Agnes W.; Bos, Lieuwe D.; van der Schee, Marc P.; van Schooten, Frederik-Jan; Sterk, Peter J.
Abstract : Medical diagnosis and phenotyping increasingly incorporate information from complex biological samples. This has promoted the development and clinical application of non-invasive metabolomics in exhaled air (breathomics). In respiratory medicine, expired volatile organic compounds (VOCs) are associated with inflammatory, oxidative, microbial, and neoplastic processes. After recent proof of concept studies demonstrating moderate to good diagnostic accuracies, the latest efforts in breathomics are focused on optimization of sensor technologies and analytical algorithms, as well as on independent validation of clinical classification and prediction. Current research strategies are revealing the underlying pathophysiological pathways as well as clinically-acceptable levels of diagnostic accuracy. Implementing recent guidelines on validating molecular signatures in medicine will enhance the clinical potential of breathomics and the development of point-of-care technologies. Trends: Regarding metabolomics in exhaled air, the clinical application of VOCs for diagnosing and phenotyping holds most potential. VOCs can serve as non-invasive biomarkers of inflammatory, oxidative and neoplastic processes. Separating VOCs based on source is not always mandatory, but depends on the application. Although understanding the biochemical pathway underlying a VOC is required for pathophysiological understanding, probabilistic analysis of exhaled breath already exhibits diagnostic accuracy. Breath sampling affects the exhaled VOC spectrum and requires standardization. To this end, two international initiatives are currently under development. To fulfill the clinical promise of breathomics, the currently-available studies showing moderate to good diagnostic accuracy demand external validation.